PREPARATION AND CHARACTERIZATION OF POLYMER COMPOSITE TILE BASED ON BOILER ASH WASTE FROM PALM OIL INDUSTRY AND FIBER FROM WASTE TIRE REINFORCED BY ASPHALT - Awan Maghfirah; Anwar Dharma Sembiring; Mulkan Iskandar Nst (FISITEK: Jurnal Ilmu Fisika dan Teknologi, 2018)
Polymer composite tile based on boiler ash waste from palm oil industry (ABKS) and fiber from waste tire reinforced by asphalt have been prepared through compression molding techniques. The raw materials consist of sand, ABKS, recycled tire fibers, asphalt, and epoxy resin with variation of ABKS and recycled tire fibers composition by 20%:0%, 18%:2%, 16%:4%, 14%:6%, 12%:8%, and 10%:10%. The characterization performed includes: physical properties (density and water absorption), mechanical properties (compressive strength, impact strength, and flexural strength), and thermal properties (DTA, Differential Thermal Analysis). The test results showed that sample with the optimum composition of sand, ABKS, recycled tire fibers, asphalt, and epoxy resin of 55%: 12%: 8%: 10%: 15% had the highest density value of 1.64 grams/cm3, water absorption of 1.72%, impact test value of 77.68 kJ/m2, bending strength value of 19.373 MPa, and DTA temperature of 360 ºC. These results meet SNI standards for existing tiles and can be used as an alternative tile materials which is affordable and environmentally friendlyKeywords: Boiler ash waste from palm oil industry (ABKS), polymer composite tile, and recycled tire fibers